Suitability of chrysophyllum albidum wood for fabrication of howe truss for use in simple roof systems (2010)
Chrysophyllum albidum being fruit tree still has dearth of information about its wood properties. Its use for making roof truss components have become fashionable in low cost building in emerging areas of Akinyele Local Government, Ibadan, Oyo State, Nigeria because of its abundance. This study was initiated to investigate the suitability of C. albidum wood for Howe truss fabrication. A survey was conducted to obtain on the application status of C. albidum wood in the study location. Structured questionnaire, oral interview and on-spot assessment were used to collect data while simple descriptive statistical tools were used for the data analysis. 10-meter-span Howe-truss was designed but scaled down to 2-meter for prototype production. Six prototypes were fabricated using C. albidum wood bought from a plank market in the area. The deflection characteristics of the fabricated truss was investigated under three points loading system using dial-gauge. Modified Howe truss was predominantly used in low cost building in the emerging areas of Akinyele Local Government that were hitherto villages. About 90.1% of such houses combined C. albidum wood with other available wood species to make its roof trusses. C. albidum wood was relevant for its availability and cost. The gusset plate made from 6.5mm structurally graded plywood was used at the joint with 8d nail as fastener. The fabricated Howe truss weighs 1.2KN. A load of 2.2KN (about triple of the design load) was only able to cause maximum of 3.3mm deflection as against maximum tolerable deflection of 6.6mm. The test result indicates suitability of C. albidum wood for Howe truss production despite it been perishable when used in contact with soil.